The scarred woman [compact disc, unabridged] : a Department Q novel - Adler-Olsen, Jussi (The Department Q series, 2017)
Detective Carl Mørck of Department Q, Copenhagen's cold-cases division, meets his toughest challenge yet when the troubled past of a team member collides with a sinister unsolved murder. Failure to meet his superiors' expectations will mean the end of Department Q.